Air quality control handbook (McGraw-Hill, 1998)
Covering the details of the 1990 Clean Air Act, this work offers an overview of air pollution control management, discusses the sources and effects of air pollution and its effects on the environment, and explains the available pollution treatment and control technologies. It includes air-moving, vapor, and particulate control equipment.